COMBINED TREATMENT OF PATIENTS WITH NON-SMALL CELL LUNG CANCER WITH PERSONALIZED PRESCRIPTION OF ADJUVANT CHEMOTHERAPY - E.O. RODIONOV; S.V. MILLER; L.A. EFTEEV; S.A. TUZIKOV; M.M. TSYGANOV; I.V. DERYUSHEVA; N.V. LITVYAKOV; V.A. MARKOVICH; U.B. URMONOV (Avicenna Tajik State Medical University, 2019)
Objective: To study the long-term results of the combined treatment of non-small cell lung cancer (NSCLC) using pre-surgery chemotherapy, radical surgery and personalized adjuvant chemotherapy based on the level of monoresistance genes. Methods: Four-year results of treatment of 72 patients of NSCLC II-III stage were analyzed. All patients underwent 2 courses of neoadjuvant chemotherapy (vinorelbine/carboplatin) and surgical treatment. Personalized adjuvant chemotherapy based on the levels of expression of monoresistance genes АВСС5, RRM1, TYMS, TOP1, TOP2α, TUBB3, BRCA1, and ERCC1 was performed in the main group (n=35). Three courses of adjuvant chemotherapy (vinorelbine/carboplatin) were performed in the control group (n=37). Results: In the main group the progression of the disease was observed in 14 out of 35, and in the control group - in 21 out of 37 patients. Relapsefree survival (RFS) in the main group was 60.0% (95% CI: 43.6-74.5), in the control group - 43.2% (95% CI: 28.7-59.1); Log-Rank test χ2 =3,071, р=0,080; RR=1,808 (95% CI: 0.918-3.561). The median RFS in the control group was 27 months (95% CI: 5.7-48.3). The overall survival rate in the main group was 77.1% (95% CI: 61.0-87.9), in the control group - 54.1% (95% CI: 38.4-69.0); Log-Rank test χ2 =2,813, p=0.094; RR=2,024 (95% CI: 0,870-4,709). Conclusion: The developed method of personalized prescribing adjuvant chemotherapy to patients with NSCLC based on the molecular genetic characteristics of the tumor improves relapse-free and overall survival.